UPAYA PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KORUPSI DI INDONESIA - Umacina, Nurhidayat; Amsori, Amsori (Postulat, 2024)
Corruption in Indonesia is a complex and profound problem, hindering development and damaging public trust in state institutions. Law enforcement efforts against corruption have been regulated in various regulations, including Law No. 31 of 1999 concerning the Eradication of Corruption, and strengthened by the existence of the Corruption Eradication Commission (KPK). Although the legal framework has been prepared, significant challenges are still faced, such as low human resource capacity, lack of coordination between institutions, and an internalized culture of corruption. The formulation of the problem is 1) How is transparency regulated in preventing corruption? 2) What are the obstacles to transparency in efforts to prevent corruption in government? The research method used is normative juridical. The results of the study show that Indonesia still faces great difficulties in eradicating corruption. Although there have been various efforts, the increase in cases and state losses caused by corruption are still a major problem in Indonesia. There are regulations and policies to overcome corruption and punish perpetrators of corruption, but the implementation of regulations and policies still has many shortcomings so that their effectiveness has not been felt greatly.